Parallel ‘go with the winners’ algorithms in distributed memory models - Peinado, Marcus; Lengauer, Thomas (Journal of parallel and distributed computing, 2003)
We parallelize the ‘go with the winners’ algorithm of Aldous and Vazirani (in: Proceedings of the 35th IEEE Symposium on the Foundations of Computer Science, IEEE Computer Society Press, Silver Spring., MD, 1994, pp. 492–501) and analyze the resulting parallel algorithm in the LogP-model (in: Proceedings of the Fourth ACM SIGPLAN Symposium on Principles & Practice of Parallel Programming, 1993, pp. 1–12). The main issues in the analysis are load imbalances and communication delays. The result of the analysis is a practical algorithm which, under reasonable assumptions, achieves linear speedup. Finally, we analyze our algorithm for a concrete application: generating models of amorphous chemical structures.